An assessment of the investment climate in Nigeria - Iarossi, Giuseppe; Mousley, Peter, 1956-; Radwan, Ismail; World Bank. (Washington, DC : World Bank, 2009)
"Nigeria's Vision 2020 has expressed a bold desire for the country to be among the world's top 20 economies by the year 2020. The economy has posted impressive growth figures since 2003, driven by higher oil revenues and a series of home-grown economic reforms. The country is now firmly on the road to middle income status. But what else do government and the private sector need to do to create the jobs and growth that will underpin the national development strategy? What are the challenges that Nigeria's businesses face today? An Assessment of the Investment Climate in Nigeria provides answers to these questions. Based on a survey of 2,300 companies, it provides evidence-based recommendations designed to support Vision 2020 and the president's seven-point agenda."
"The authors find that government must move quickly to create jobs and reduce poverty. Key challenges include a desperate shortage of energy and a poor transportation network, as well as low levels of education and continuing unrest in the Niger delta. In addition, Nigeria's workers need to become more productive in order to compete in a globalized economy."--BOOK JACKET.
Ch. 1. Firm Productivity in Nigeria -- Ch. 2. The Business Environment in Nigeria -- Ch. 3. Comparing the State-Level Investment Climate -- Ch. 4. Access to Finance -- Ch. 5. Entrepreneurship and Managerial Capacity in Nigerian Firms -- Ch. 6. Other Aspects of the Investment Climate: Functioning of the Labor Market, Micro Enterprises, and Gender Differences -- Ch. 7. Conclusions - Framing a Policy Response -- App. 1. Sample Composition -- App. 2. Constructing a Composite Investment Climate Index.
Includes bibliographical references (p. 105-106) and index.
Keywords: Investments -- Nigeria